Developing Discovery-Based Reading Assessment to Stimulate Students’ Critical Thinking and Creativity in English Learning - Waluyo, Yenni Desnia (Universitas Negeri Semarang, 2018)
Education in Indonesia needs the activities to build students’ thinking skill and creativity. Therefore, this study is conducted to develop discovery-based-reading assessment to stimulate the students’ critical thinking and creativity in English learning. This study uses research and development (R & D) at X IPS 2 of SMA N 15 Semarang. The data are gathered through interview, questionnaire, and observation which are aimed to know the existing of the implementation of HOT discovery learning assessment. Meanwhile, the data from pre-test and post-test are gotten by answering questions to measure the students’ learning achievement. During the implementation of assessment, the teacher provides some problems and then the students mobilize their whole thinking and skill to solve the problems. The results indicate that the implementation of discovery-based-reading assessment successfully stimulate the students’ critical thinking and creativity in English learning. Further, the results also show the students’ scores improvement of pre-test and post-test where the reading skill is 67.00 to 88.38. Moreover, the students participate in the process of teaching and learning actively. They are able to work in a group discussion to solve the problems and answer the queestions correctly. Finally, their cognitive ability can be acute. In conclusion, the HOT discovery- based-reading assessment is applicable to stimulate the students’ critical thinking and creativity in English learning.